Village Financial Accountability through Siskeudes: A Case Study in Jambur Pulau - Ade Trya Amelia; Nursanti Yanti; Nurwani (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze how the implementation of Government Accounting Standards (SAP), supported by the Village Financial Management System (SISKEUDES), can improve accountability in village financial management. This study used a qualitative approach with a descriptive qualitative approach. Data were obtained through interviews with several informants, observations, and documentation. The informants in this study were the village head, the village secretary, and the village finance officer. The data analysis technique used was triangulation, which encompasses three stages: data reduction, data presentation, conclusion drawing, and verification. The results indicate that the implementation of Government Accounting Standards (SAP) through the Siskeudes application in Jambur Pulau Village has been successful and supports transparent, orderly, and accountable financial management. Siskeudes has proven effective in strengthening village financial accountability and facilitating the preparation of financial reports in accordance with regulations, although technical challenges and limited human resources remain. Regular training and mentoring help improve the skills of village officials in operating the application.